ILLUMINATING Al-ḤAQQ: Unveiling Truth and Reality in Ibn Barrajân's Sufi Paradigm and Systems Thinking - Fahrudi, Ah. Haris; Riyadi, Abdul Kadir; Mursyid, Achmad Yafik; Muttaqin, Sabilil (Ulul Albab: Jurnal Studi Islam, 2023)
The concept of al-haqq represents a foundational yet underexplored dimension in the philosophical discourse of Sufism. Despite its centrality, systematic elaborations on al-h{aqq remain limited within classical Sufi scholarship. This article examines the significant contribution of Ibn Barrajân, a prominent Andalusian Sufi thinker, to the development of the concept through his unique tawhîd paradigm. Adopting a systems approach, the study analyzes Ibn Barrajān’s metaphysical interpretation of al-haqq, revealing a comprehensive framework that integrates ontology (unity of reality), epistemology (unity of knowledge), and axiology (unity of purpose). This triadic structure forms the basis of Ibn Barrajân’s multidimensional and goal-oriented view of existence, rooted in divine unity. Al-haqq, in his thought, emerges as the ultimate ontological reality and the objective of all intellectual and spiritual endeavors. Epistemologically, the knowledge of al-haqq is pursued through contemplation of the manifestations of God’s Names within cosmic signs, facilitated by the spiritual practices of tafakkur (reflection), tadhakkur (remembrance), tadabbur (deep thinking), and iʿtibâr (consideration). Axiologically, this knowledge is not merely theoretical but is to be actualized through the embodiment of wisdom (hikmah) as practiced in the sunnah. The study highlights the urgent need to revisit and engage with Ibn Barrajân’s integrative metaphysical insights, which offer a holistic model for understanding reality and its divine purpose. By articulating al- haqq as both the ground and goal of knowledge, Ibn Barrajān’s thought contributes significantly to Sufi philosophy and invites deeper exploration of divine-centered epistemology in Islamic intellectual tradition.